Strategi Manajemen Kualitas Air Di Perairan Umum Untuk Mendukung Kehidupan Akuatik - zebua, Hertini; Halawa, Eduardus Heronimus (CV. SINAR HOWUHOWU, 2025)
Water quality management in public waters is a crucial aspect of maintaining ecosystem balance and the sustainability of aquatic resources. This study examines key water quality parameters such as temperature, pH, dissolved oxygen, and organic matter content, as well as their impact on aquatic life. Data were collected through field surveys and laboratory analyses at various public water locations. Results indicated significant variations in water quality, largely influenced by anthropogenic activities such as agriculture and industry. The study recommends sustainable management strategies to preserve water quality and support aquatic ecosystem conservation.